MODEL;PEMBELAJARAN;KOOPERATIF;TIPE;THINK;PAIR;SQUARE UNTUK;MENINGKATKAN;KEMAMPUAN KOMUNIKASI;MATEMATIS - TIARA NOVESYA (Departemen Matematika, 2018)
Themathematical communication of ability is the goals of one of mathematics learning. In fact, student’s mathematical communication class VIII SMPN 7 Padang is not optimal. This is can see at the time of observation and test score given to students that contain indicator of the ability of mathematical communication is low.One effort that can be done to apply cooperative learning model type TPSq. The purpose of this study is to look at differences in mathematical communication skills of learners using learning model of cooperative type TPSq with learners who learning directly. This type of research used is quasi experimental with the design of research Randomized Control-Group Only Design and Descriptive. The research instrument is a quiz and tests the ability of mathematical communication in the form of essay matter. The results a quiz showed that the mathematical communication ability of learners using cooperative model of TPSq type is best andthe results showed that the mathematical communication ability of learners using cooperative model of TPSq type is better than the mathematical communication ability of the students whose learning using direct learning.Keywords – Cooperative;learning;type;TPSq, Student’s;mathematics;communication;skills, Direct Instruction